Ownership and Production Costs - Choosing Between Public Production and Contracting Out - Henry Ohlsson (Uppsala University, Department of Economics, 1998)
Many comparisons of the performance of public and private producers use a public/private ownership dummy variable to capture cost differences in cross section data. This is appropriate if the producer choice is random. The dummy variable model is, however, logically inconsistent if the producer choice depends on cost differences. If cost differences do not matter for choice, there is still a risk for selectivity bias if there are other variables affecting the producer choice. I compare public and private enterprises using refuse collection costs in 115 Swedish municipalities. The data cover 170 enterprises. First, I find that cost differences do not affect producer choice. Second, producer choice is important for costs. Third, the cost advantage found for private firms using the dummy variable model disappears when choice is taken into account. Fourth, the parameters of the cost functions differ between private and public firms.
urn:nbn:se:uu:diva-2406
Keywords: D24; E22; L32; L33; 330; public ownership; private ownership; competitive tendering; contracting out; cost minimization; switching regression model with endogenous switching; privatization